Factors associated with undernutrition among pregnant women in Haramaya district, Eastern Ethiopia: A community-based study - Meseret Belete Fite; Abera Kenay Tura; Tesfaye Assebe Yadeta; Lemessa Oljira; Kedir Teji Roba (PLoS ONE, 2023)
Introduction Although undernutrition in pregnancy has continued to get global attention as pregnancy is considered a critical period in the life cycle owed to increase the metabolic and physiological demands, evidence is scarce on undernutrition and associated factors among pregnant women in eastern Ethiopia. Therefore, this study assessed the undernutrition and associated factors among pregnant women in Haramaya district, Eastern Ethiopia. Methods A community-based cross-sectional study was conducted among randomly selected pregnant women in Haramaya district, eastern Ethiopia. Data were collected through face-to-face interviews, anthropometric measurement, and hemoglobin analysis by trained research assistants. An adjusted Prevalence ratio (aPR), and a 95% confidence interval (CI), were used to report associations. Poisson regression analysis model with a robust variance estimate identified variables associated with undernutrition. Data were double entered using Epi-data 3.1 and cleaned, coded, checked for missing and outliers, and analyzed using Stata 14 (College Station, Texas 77845 USA. Finally, the p-value <0.05 was the cut-off point for the significant association. Results A total of 448 pregnant women with a mean age of 25.68 (± 5.16) were included in the study. The prevalence of undernutrition among pregnant women was 47.9% (95% CI: 43%-53%). From the analysis, the undernutrition was more likely higher among respondents who had five or more family members (APR = 1.19; 95% CI = 1.02–1.40), lower dietary diversity (APR = 1.58; 95% CI = 1.13–2.21) and those who were anemic (APR = 4.27; 95% CI = 3.17–5.76). Conclusion Nearly half of the pregnant women in study area were undernourished. High prevalence was found among women who had large family sizes, low dietary diversity and anemia during pregnancy. Improving dietary diversity, strengthening family planning services and giving special attention to pregnant women, supplementation of iron and folic acid, and early detection and treatment of anemia is essential to improve the high burden of undernutrition and the adverse effect on pregnant women and the fetus.